Tantangan Pancasila sebagai ideologi bangsa dalam upaya pemberantasan korupsi dan penguatan moderasi beragama - Bella, Silvia Salsa; Kholidiyah, Ayus Sa'adatil; Romadhoni, Rahma; Azkiyah, Alya Qolbiyatul; Arobi, Muhammad Laudza'ul (Maliki Interdisciplinary Journal, 2025)
Pancasila as the ideology of the Indonesian nation has a vital role in shaping the basis of the life of the nation and state. In the midst of the development of the times and the complexity of national problems, the two main issues that need special attention are the eradication of corruption and the strengthening of religious moderation. These two things are interrelated and have the potential to shake the socio-political stability of the nation if not addressed properly. This research aims to find out the historical, sociological, and political aspects of Pancasila as the ideology of the State, the ideology of Pancasila in religious moderation, and the efforts made in eradicating / preventing corruption. This research method uses a literature review. Pancasila remains relevant as a guideline for the Indonesian nation in facing these challenges. The eradication of corruption and the strengthening of religious moderation can be carried out by strengthening the law enforcement system, moral education based on Pancasila, and the active involvement of the community and religious leaders in maintaining national values. With synergy between various elements of the nation, Pancasila can continue to be a solid guideline in building a just, prosperous, and tolerant Indonesia.